Comparison of Incidence of Laryngospasm between Laryngeal Mask Airway and Endotracheal Tube during the Recovery Phase following Urological Procedure in Paediatric Patients (Community Based Medical Journal, 2024)
Airway-related issues pose significant perioperative complications in paediatric anaesthesia, with laryngospasm being particularly noteworthy. The choice of airway device has been identified as a contributing factor to this concern. This research was conducted from January to December of 2023; it specifically investigated and compared the incidence of laryngospasm following removal of a laryngeal mask airway (LMA) versus an endotracheal tube (ET) in paediatric patients undergoing elective urological procedure. Sixty ASA – I/II patients, aged 2 to 5 years and of both genders, were randomly allocated into two groups: Group I received ETT, while Group II received LMA. Various parameters including hemodynamic measures and the occurrence of laryngospasm, cough, and other complications were assessed. Results demonstrated a higher incidence of laryngospasm and cough in the ET group compared to the LMA group (p